The role of the church in preparing congregations to face Covid-19 and life after the pandemic in Zimbabwe - Rudo Mukurazhizha; Francis Maushe (Academia Publishing, 2023)
The role of the church in responding to pandemics has become a mainstay of the health care stem globally. Five faith leaders from three Evangelical churches, one Pentecostal and one Apostolic Church participated in this qualitative study and fifteen other members of the churches in the sample. Using telephone interviews as a method of elicitation, participants experience with life during COVID-19 pandemic informed this exploration. Results suggested that the church provided a framework for interpretation and mitigation from COVID-19 pan-demic and has a key role in responding to disaster situations. The paper underscores the urgent need for a holistic approach between disasters support systems and faith leaders to increase disaster preparedness within faith communities which fosters community wide disaster risk reduction.